2008
DOI: 10.1177/0003319707303887
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Relationship Between Myocardial Perfusion Imaging and Coronary Artery Disease Risk Factors and Markers of Inflammation?

Abstract: The treatment of coronary artery disease (CAD) is clinically measured by monitoring changes in venous lipids and inflammatory markers. There is currently no established quantified relationship between coronary flow reserve and markers of inflammatory CAD. A total of 120 men and women underwent quantified measurement of coronary blood flow using SPECT imaging at baseline and 1 year later. They had fasting venous blood work obtained at baseline and 1 year later. These markers of lipids and inflammation included,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…A further study demonstrated elevated homocysteine levels with reduced regional left ventricular ejection fraction in an asymptomatic group of young patients,1 while others found a high prevalence of patients with elevated homocysteine levels in patients with heart failure with preserved ejection fraction 15. This was similar to the figures we obtained where the presence of infarct seemed to have more influence on homocysteine levels than ischaemia.…”
Section: Discussionsupporting
confidence: 85%
“…A further study demonstrated elevated homocysteine levels with reduced regional left ventricular ejection fraction in an asymptomatic group of young patients,1 while others found a high prevalence of patients with elevated homocysteine levels in patients with heart failure with preserved ejection fraction 15. This was similar to the figures we obtained where the presence of infarct seemed to have more influence on homocysteine levels than ischaemia.…”
Section: Discussionsupporting
confidence: 85%
“…Comparison of the rest/stress image results with the angiographic results showed a sestamibi rest/stress imaging sensitivity of 67%. Of the false negative results (n = 22), 18% (n = 4) had critically narrowed arteries or arteries with vulnerable plaques whose 60-minute images appeared completely normal (Pace 2005, Fleming 2008). However, evaluation of the 5-minute images for redistribution (using FHRWW), revealed both qualitative and quantitative decreased uptake, demonstrating a washin effect.…”
Section: Resultsmentioning
confidence: 99%
“…The receptor for IL-6 is also a target of prevention of coronary vascular diseases (6). Conversely, the relationship between inflammatory markers and myocardial single photon emission computed tomography (SPECT) findings remains somewhat controversial (7). Annals of Nuclear Cardiology Vol.…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%